Análise com acoplamento hidromecânico da barragem Cipoada (CE) considerando a influência de zonas não saturadas no Comportamento do maciço compactado - Abreu, Ammanda Aragão (2021)
Hydromechanical coupling and the adoption of a constitutive model for non-soils saturated in earth dams allow a more realistic analysis of their behavior, bearing in mind that the saturated and unsaturated flow occurs permanently during its operation, changing the state of stresses of the massif and causing deformations. This research consisted of carrying out an analysis with hydromechanical coupling of the Cipoada dam, located in Morada Nova (CE), considering the existence of unsaturated areas in the massif compressed. For this, the BBM model (Barcelona Basic Model) was used, which adopts a elastoplastic relationship for unsaturated soils proposed by Alonso, Gens and Josa (1990). You mechanical and hydraulic parameters of the soil, necessary for carrying out the simulation numerical data, were determined from the execution of a series of laboratory tests (characterization tests, filter paper, direct shear, edometric densification and permeability). For conducting the direct shear and densification tests edometric method, we opted for a simplified methodology, without the suction control, due to unavailability of equipment with this technology. The simplification used consisted of carrying out tests with known humidity, in which the suction of the tested sample was determined from the soil water retention curve. The coupled analysis of the dam Cipoada was performed in the finite element program CODE_BRIGHT (COupled DEformation and BRine, Gas and Heat Transport) and consisted of the simulation of the filling and emptying the reservoir, using the actual water storage volumes from 1992 to 2016. From the coupled simulation performed, it was possible to analyze the effect of the variation of the poropressure in the stresses and deformations of the massif, as well as to analyze the influence of volumetric deformations on soil porosity. The results showed that the BBM model satisfactorily described the behavior of the dam. It was verified at certain points chosen in the massif, that during filling, the soil presented plasticization when subjected to a trajectory of increased tension and decreased suction. During emptying, at these points, the soil returned to the elastic domain when subjected to to a trajectory of reduced tension and increased suction. It was also found that the internal drainage system of the dam significantly influenced the behavior hydromechanical of the massif and a possible improper functioning leads to an increase of up to 75% in the total displacements of the dam.